Question
upstudy study bank question image url

c) If \( 2 \tan 2 \theta=-\sqrt{5} \) with \( 0^{\circ}<2 \theta<180^{\circ} \), determine the value of the following without th of a calculator and with the aid of a diagram: \( \begin{array}{ll}\text { (1) } \sin 2 \theta & \text { (2) } \sin \theta \cos \theta \\ \text { (4) } \cos \theta & \end{array} \)

Ask by Gough Black. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \begin{array}{ll} (1) & \sin 2\theta = -\frac{4\sqrt{5}}{9} \\ (2) & \sin \theta \cos \theta = -\frac{2\sqrt{5}}{9} \\ (4) & \cos \theta = \frac{\sqrt{5}}{3} \\ \end{array} \]

Solution

To solve the problem, we start with the equation given: \[ 2 \tan 2\theta = -\sqrt{5} \] From this, we can express \(\tan 2\theta\): \[ \tan 2\theta = -\frac{\sqrt{5}}{2} \] ### Step 1: Determine the angle \(2\theta\) Since \(0^{\circ} < 2\theta < 180^{\circ}\), we know that \(2\theta\) is in the first or second quadrant. The tangent function is negative in the second quadrant. Therefore, we can find \(2\theta\) as follows: Let \(2\theta = 180^{\circ} - \alpha\), where \(\tan \alpha = \frac{\sqrt{5}}{2}\). To find \(\alpha\), we can use the tangent inverse: \[ \alpha = \tan^{-1}\left(\frac{\sqrt{5}}{2}\right) \] Thus, \[ 2\theta = 180^{\circ} - \alpha \] ### Step 2: Calculate \(\sin 2\theta\) Using the identity for sine in terms of tangent: \[ \sin 2\theta = \frac{2 \tan 2\theta}{1 + \tan^2 2\theta} \] First, we calculate \(\tan^2 2\theta\): \[ \tan^2 2\theta = \left(-\frac{\sqrt{5}}{2}\right)^2 = \frac{5}{4} \] Now substituting into the sine formula: \[ \sin 2\theta = \frac{2 \left(-\frac{\sqrt{5}}{2}\right)}{1 + \frac{5}{4}} = \frac{-\sqrt{5}}{\frac{9}{4}} = -\frac{4\sqrt{5}}{9} \] ### Step 3: Calculate \(\sin \theta \cos \theta\) Using the double angle identity: \[ \sin 2\theta = 2 \sin \theta \cos \theta \] Thus, \[ \sin \theta \cos \theta = \frac{\sin 2\theta}{2} = \frac{-\frac{4\sqrt{5}}{9}}{2} = -\frac{2\sqrt{5}}{9} \] ### Step 4: Calculate \(\cos \theta\) Using the identity: \[ \cos^2 2\theta + \sin^2 2\theta = 1 \] We already have \(\sin 2\theta\), so we can find \(\cos 2\theta\): \[ \cos 2\theta = \sqrt{1 - \sin^2 2\theta} = \sqrt{1 - \left(-\frac{4\sqrt{5}}{9}\right)^2} \] Calculating \(\sin^2 2\theta\): \[ \sin^2 2\theta = \left(-\frac{4\sqrt{5}}{9}\right)^2 = \frac{80}{81} \] Now substituting back: \[ \cos 2\theta = \sqrt{1 - \frac{80}{81}} = \sqrt{\frac{1}{81}} = \frac{1}{9} \] Using the double angle formula for cosine: \[ \cos 2\theta = 2 \cos^2 \theta - 1 \] Setting this equal to \(\frac{1}{9}\): \[ 2 \cos^2 \theta - 1 = \frac{1}{9} \] Solving for \(\cos^2 \theta\): \[ 2 \cos^2 \theta = \frac{1}{9} + 1 = \frac{10}{9} \] \[ \cos^2 \theta = \frac{5}{9} \] Thus, \[ \cos \theta = \sqrt{\frac{5}{9}} = \frac{\sqrt{5}}{3} \] ### Summary of Results 1. \(\sin 2\theta = -\frac{4\sqrt{5}}{9}\) 2. \(\sin \theta \cos \theta = -\frac{2\sqrt{5}}{9}\) 3. \(\cos \theta = \frac{\sqrt{5}}{3}\) Final answers: \[ \begin{array}{ll} (1) & \sin 2\theta = -\frac{4\sqrt{5}}{9} \\ (2) & \sin \theta \cos \theta = -\frac{2\sqrt{5}}{9} \\ (4) & \cos \theta = \frac{\sqrt{5}}{3} \\ \end{array} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( 2 \tan 2\theta = -\sqrt{5} \), we first have: \[ \tan 2\theta = -\frac{\sqrt{5}}{2}. \] This tells us that \( 2\theta \) lies in the second quadrant, where tangent is negative. We can find \( 2\theta \) by using the reference angle technique. The reference angle when \( \tan^{-1}\left(\frac{\sqrt{5}}{2}\right) \) is calculated to find an angle \( \alpha \). Therefore, we have: \[ 2\theta = 180^\circ - \alpha. \] From this relationship, we can find \(\sin 2\theta\): 1. When \( 2\theta = 180^\circ - \alpha\), we use: \[ \sin 2\theta = \sin (180^\circ - \alpha) = \sin \alpha. \] Given that \(\tan \alpha = \frac{\sqrt{5}}{2}\), we can use the Pythagorean identity to find \(\sin \alpha\): \[ \sin^2 \alpha + \cos^2 \alpha = 1, \] where \(\sin \alpha = \frac{\sqrt{5}}{\sqrt{5^2 + 2^2}} = \frac{\sqrt{5}}{\sqrt{25 + 4}} = \frac{\sqrt{5}}{\sqrt{29}}.\) Thus: \[ \sin 2\theta = \frac{\sqrt{5}}{\sqrt{29}}. \] 2. The next part involves finding \(\sin \theta \cos \theta\). We can utilize the identity: \[ \sin 2\theta = 2 \sin \theta \cos \theta. \] So: \[ 2 \sin \theta \cos \theta = \frac{\sqrt{5}}{\sqrt{29}} \implies \sin \theta \cos \theta = \frac{\sqrt{5}}{2\sqrt{29}}. \] 3. Finally, we need to determine \( \cos \theta \). Since \( \tan 2\theta = -\frac{\sqrt{5}}{2}\), and we know \(\sin 2\theta\), we can find \(\cos 2\theta\): \[ \cos 2\theta = -\frac{2}{\sqrt{29}} \quad \text{(since } \tan 2\theta = \frac{\sin 2\theta}{\cos 2\theta}). \] Then using the half-angle identity: \[ \cos^2 \theta = \frac{1 + \cos 2\theta}{2} = \frac{1 - \frac{2}{\sqrt{29}}}{2} = \frac{\sqrt{29} - 2}{2\sqrt{29}}. \] By calculating square roots, we find \(\cos \theta\). Thus the values are: 1. \( \sin 2 \theta = \frac{\sqrt{5}}{\sqrt{29}} \) 2. \( \sin \theta \cos \theta = \frac{\sqrt{5}}{2\sqrt{29}} \) 3. \( \cos \theta = \text{found from half-angle identity} \) clarifies the relationship depending on quadrant constraints.

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy